2010
DOI: 10.21273/hortsci.45.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Tetraploidy to Feverfew (Tanacetum parthenium Schulz-Bip.): Morphological, Physiological, Cytological, and Phytochemical Changes

Abstract: An efficient colchicine-mediated chromosome doubling of diploid feverfew followed by the morphophenological, physiological, phytochemical, and cytological changes of the obtained tetraploid plants was conducted. One-week-old seedlings of feverfew were treated with 0.05% (w/v) colchicine for 2, 4, 6, 8, and 24 h. Tetraploid plants were regenerated after 4 months, showing significant changes in stomatal size and density; sizes of seed; flower, pollen, leaf, trichome, cell, nucleus, and parthenolide conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
33
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 27 publications
11
33
0
2
Order By: Relevance
“…Our analysis indicates that chromosome doubling has a significant influence on secondary metabolite concentrations. Similar results have been reported for other plant species (Banyai et al, 2010;Majdi et al, 2010;Mishra et al, 2010;Caruso et al, 2011;Dehghan et al, 2012;Abdoli et al, 2013;Lavania, 2013;Dixit and Chaudhary, 2014). Phenolic compounds are active in pathogen resistance, pigment production, and protection against ultraviolet radiation (Winkel-Shirley, 2001); they also qualitatively and quantitatively improve the biochemical profile of plants (Maruška et al, 2010).…”
Section: Phenolic Compounds In Triploid and Hexaploid M × Giganteussupporting
confidence: 80%
“…Our analysis indicates that chromosome doubling has a significant influence on secondary metabolite concentrations. Similar results have been reported for other plant species (Banyai et al, 2010;Majdi et al, 2010;Mishra et al, 2010;Caruso et al, 2011;Dehghan et al, 2012;Abdoli et al, 2013;Lavania, 2013;Dixit and Chaudhary, 2014). Phenolic compounds are active in pathogen resistance, pigment production, and protection against ultraviolet radiation (Winkel-Shirley, 2001); they also qualitatively and quantitatively improve the biochemical profile of plants (Maruška et al, 2010).…”
Section: Phenolic Compounds In Triploid and Hexaploid M × Giganteussupporting
confidence: 80%
“…The enlarged stomata and pollen grains of induced doubled haploid plants reported in our study have alson bee observed in other plants (Takamura and Miyajima 1996;Thao et al 2003;Majdi et al 2010). In the present study, an increased ploidy level was correlated with a larger size of the guard cells and a lower density of leaf stomata.…”
Section: Discussionsupporting
confidence: 89%
“…The mobile phase was an isocratic 55 % acetonitrile: 45 % water at 1.5 ml/min flow rate for 5 min. The UV detector was set at 210 nm (Majdi et al 2010).…”
Section: Quantification Of Parthenolidementioning
confidence: 99%